Atlas of Head/Neck and Spine Normal Imaging Variants - McKinney, Alexander (Springer International Publishing, 2018)
This text provides a comprehensive overview of the normal variations of the neck, spine, temporal bone and face that may simulate disease. Comprised of seven chapters, this atlas focuses on specific topical variations, among them head-neck variants, orbital variants, sinus, and temporal bone variants, and cervical, thoracic, and lumbar variations of the spine. It also includes comparison cases of diseases that should not be confused with normal variants. Atlas of Head/Neck and Spine Normal Imaging Variants is a much needed resource for a diverse audience, including neuroradiologists, neurosurgeons, neurologists, orthopedists, emergency room physicians, family practitioners, and ENT surgeons, as well as their trainees worldwide.